Atomized Lead Free Solder Alloys For Solder Paste Product For Electronic Application - Bakir, Mohammed Luay (2012)
Properties of Sn-9Zn and Bi-48.8In-19.6Sn solder alloys have been investigated along with Sn-40Pb as a reference. The solder alloys where characterized (density, XRD, SEM, CTE and DSC) before the atomization process. The characterized solder alloys are then gas atomized at a pressure of 0.4 MPa and superheat temperature of 20% above their respective liquidus temperature obtained from the DSC analysis. Solder powders are then sieved and characterized using SEM and particle size analyzer. The characterized powders of size +75-150 μm are then mixed with zinc chloride flux at different metal to flux ratios (90:10, 80:20, 70:30, and 60:40). The wetting properties (spreading and contact angle), interfacial reactions and mechanical property (shear test) of the solder pastes are then studied. The Sn-40Pb solder paste demonstrates the highest spreading and lowest contact angle compared to Sn-9Zn and Bi-48.8In-19.6Sn. At the solder/substrate interface, the intermetallic compound Cu6Sn5 was formed for both Sn-40Pb and Bi-48.8In-19.6Sn regardless of metal content and Sn-Cu-Zn intermetallic compound is formed at the Sn-9Zn (90 wt%)/Cu interface. The highest joint shear strength was achieved by Sn-9Zn (90 wt%) at a value of 45.3 MPa. The shear strength increased as the metal content increases for the Sn-40Pb and Bi-48.8In-19.6Sn solder alloys. The shear strength of Sn-40Pb (90 wt%) is higher than the shear strength of Sn-40Pb (80 wt%) and the same goes for Bi-48.8In-19.6Sn solder alloy where the shear strength of Bi-48.8In-19.6Sn (90 wt%) is higher than the shear strength of Bi-48.8In-19.6Sn (80 wt%).